ANALISIS PENGGUNAAN MEDIA JOBSHEET DENGAN BANTUAN METODE DEMONSTRASI PADA DASAR PRAKTIK BATU BETON - Desti Intan Andini (CV. ADIBA AISHA AMIRA, 2024)
This study aims to analyze the results of several journals related to the use of jobsheets with the help of demonstration methods on the basis of concrete stone practice. This study was conducted to see the differences in the results of validation of the feasibility of the learning methods and media used. The method used in this study is the systematic literature review (SLR) method. Data collection in this study can be done by collecting relevant books and journals. Then the data is analyzed by reading previous research and recapitulating the results of the research seen from the effectiveness of student learning outcomes after applying the methods and media used. Based on the results of the analysis of the data obtained, the use of this demonstration method is very helpful for students in understanding the basic practice steps of concrete stone in the jobsheet. So that the demonstration method with this jobsheet media can improve student learning outcomes in the basic practice of concrete stone